Parton Densities in Quantum Chromodynamics. - Cherednikov, Igor Olegovich (De Gruyter Studies in Mathematical Physics, 2016)
The purpose of this book is to give a systematic pedagogical exposition of the quantitative analysis of Wilson lines and loops in quantum chromodynamics. Using techniques from the previous volume (Wilson Lines in Quantum Field Theory, 2014), ab initio techniques are developed and practical tools for their implementation presented. An emphasis is put on their renormalization and on implications on processes observable at experimental facilities.